In Vitro anthelminthic activity of the aqueous leaf extract of Cassia Occidentalis against Ascaris Lumbricoides - Owembabazi Annitah; Joshua Ojodale Aruwa; Jennifer Chibuogwu Ebosie; Kiiza Ronald; Neeza Timothy; Catherine Nabitandikwa; Mworozi Peter; Nkwanga John Bosco; Vian Namanya; Kaiza Allan; Ronald Kayima (German Journal of Pharmaceuticals and Biomaterials, 2025)
Intestinal nematodes affect children in impoverished populations. Conventional anthelminthic drugs have been frequently utilized to manage these infections. However, limitations such as cost, toxic effects, and resistance have shifted towards herbal medicines in low-to middle-income countries. There is a lack of evidence supporting the effectiveness of Cassia occidentalis plant leaf extract in managing helminth infections in Uganda. This study, therefore, sought to determine the phytochemical composition of Cassia occidentalis aqueous leaf extract, its acute toxicity profile, and its in-vitro anthelmintic activity against Ascaris lumbricoides. Leaves of Cassia occidentalis were collected from Bushenyi-Ishaka Municipality, dried to obtain a powder, and macerated with distilled water to create an aqueous extract. This extract underwent phytochemical screening and acute toxicity testing following established guidelines. The anthelmintic activity was evaluated using an adult worm mortality assay. The study found that the aqueous leaf extract of Cassia occidentalis had significant anthelmintic activity at a concentration of 40 mg/ml (p<0.041). Phytochemical analysis revealed the presence of alkaloids, flavonoids, tannins, saponins, and glycosides, but no steroids were found. The extract had an LD50 of over 5000 mg/kg body weight, as it caused no mortality. The study concluded that Cassia occidentalis has significant anthelmintic activity and a high LD50, supporting its traditional use in managing helminth infections.